Key technology of power big data for global real-time analysis - Guoliang ZHOU; Linjie LV; Guilan WANG (Dianxin kexue)
For power big data collected during smart grid construction process，based on the demand of power system global and real-time data analysis，ideas of solving power system security and reliability，real-time status monitoring，energy global dynamic balance scheduling and other key issues were explored. The problems of big data safety and reliability，equipment life-cycle management and energy real-time balance scheduling were analyzed and discussed，system analysis precision and accuracy based on large-scale real-time multi-source detail data and global data of equipment would be improved，then application of in-memory computing，real-time streaming data processing technology，massively parallel computing technology and column stores were explored；a layered architecture of power big data analytics platform which combined with the mainstream open source big data processing technology was proposed to provide guarantees for the efficient operation of the power system.